THE SELF: Metaphysical Reality vs Communicative Device - Tewari, Anil Kumar (Journal of Dharma, 2018)
The objective of this article is to juxtapose the nonBuddhist and the Buddhist viewpoints of Indian philosophy on the notion of the self in order to see the rationality behind their conceptions. To pursue this objective, the paper is divided into four sections. The introductory section points to various usages of the expression ‘self’ in common parlance, which tends to encompass everything that matters to an individual. The second section describes various approaches adopted by the major systems of Indian philosophy towards the self. It is shown that the conception of the self as a metaphysical substance is more amenable to those Indian philosophical systems that believe in the plurality of individual selves. The third section is mainly concerned with the Buddhist counter-narrative to the notion of substantive metaphysical self. Since the parsimony of the Buddhist proposal lies in its metaphysical non-proliferation, the linguistic entities such as the self (jīva) or soul (ātman) purportedly referring to a substantive entity are declared metaphysically vacuous, but the convention of language enables us to pick out the intended referent which is nothing but individual person. Thus the above metaphysical concepts of the non-Buddhist systems of Indian philosophy turn out to be a ’communicative device’ in Buddhism, without any metaphysical bearing.